Reestablishing Occlusal Vertical Dimension Using a Diagnostic Treatment Prosthesis in the Edentulous Patient: A Clinical Report - Keith A. Mays, DDS, MS (Journal of Prosthodontics, 2003)
To maintain a harmonious craniofacial system, the dental practitioner must establish an appropriate occlusal vertical dimension (OVD)